VD_FINDINFO Arrêt / 2025 / 352 vom 15. April 2025 - VD Tribunal cantonal (2025)
FORCE PROBANTE, ÉVALUATION DE L'INCAPACITÉ DE TRAVAIL, RAPPORT MÉDICAL | 28 al. 1 LAI, 4 al. 1 LAI, 6 LPGA, 7 LPGA, 8 al. 1 LPGA